What constitutes an equitable water share? A reassessment of equitable apportionment in the Jordan-Israel water agreement 25 years later - Talozi, S; Altz-Stamm, A; Hussein, H; Reich, P (IWA Publishing, 2019)
The water agreement between Jordan and Israel, created as part of their peace treaty in 1994, set out detailed allocations terms to which both countries have respectively abided since its inception. But after two and a half decades, the water agreement terms no longer appear as equitable considering the social, economic, and environmental changes that have occurred in the region as a whole and within the two countries individually. This paper analyzes the status of the treaty terms in light of changes seen within both countries regarding the factors laid out by the United Nations as relevant to determining equitable apportionment among riparian nations. The analysis suggests that a renegotiation of the water agreement terms is warranted due in large part to changes in population and the availability of alternative water resources (desalination and treated wastewater). While no explicit recommendations are made as to what a future treaty's terms should include, this paper presents evidence of a changing ground reality that deserves greater consideration in reaching a more equitable and sustainable water agreement for the decades to come.